Analysis of Environmental Physical-Chemical Factors and Macroalga Species In The Coastal Water of Nusalaut, Central Maluku - Indonesia - Karel Melsasail; Ali Awan; Pamella M. Papilaya (Program Pascasarjana Universitas Sriwijaya, 2018)
AbstractThe physical-chemical factors of environment are very influential on the presence and the growth of macrolaga in waters. Well-maintained water habitat is a good environment for the growth of macroalgae. A research has been conducted on the physicochemical environmental factors and the macroalgae species in the coastal waters of Nusalaut Island using transect method, and it was a survey research on four different observation stations. The results of the research showed that station I (Amet Village) has the best physicochemical factors for the presence and the growth of macroalgae, compared to station II (Nalahia Village), station III (Sila Village) and station IV (Leinitu Village). The most widely found macro algae are from the Rhodophyta class, with a total of 17 species of macroalgae, of which 15 species are found in station I. Keywords: Macroalga, environmental factors, the coastal water of Nusalaut Abstrak (Indonesian)Faktor fisik kimia lingkungan sangat berpengaruh terhadap kehadiran dan pertumbuhan makrolaga pada suatu perairan. Habitat perairan yang terjaga menjadi lingkungan yang baik bagi pertumbuhan makroalga. Telah dilakukan penelitian tentang faktor fisik kimia lingkungan dan jenis-jenis makroalga di perairan Pantai Pulau Nusalaut dengan menggunakan metode transek, dan merupakan penelitian survey pada empat stasiun pengamatan yang berbeda. Hasil penelitian menunjukkan bahwa stasiun I (Desa Amet) memiliki faktor fisik kimia terbaik bagi kehadiran dan pertumbuhan makroalga bila diabandingkan dengan stasiun II (Desa Nalahia), stasiun III (Desa Sila) dan stasiun IV (Desa Leinitu). Makroalga yang paling banyak ditemukan berasal dari kelas Rhodophyta, dengan total makroalga yaitu sebanyak 17 spesies, dimana 15 spesies diantaranya ditemukan pada satasiun I. Kata kunci: Makroalga, faktor lingkungan, perairan pantai Nusalaut